Rotational Surfaces in $\mathbb R^4$ with New Approaches and Examples - Aydın, Muhittin Evren; Rafael, Lopez (Kazım İLARSLAN, 2024)
In this paper, we give a new approach to the rotational minimal surfaces in $4$-dimensional Euclidean space $\mathbb{R}^4$. One type of these surfaces is obtained by the composition of two families of rotations in orthogonal planes. For these surfaces, we give a new parameterization. Using this parametrization, we find new examples of rotational minimal surfaces and rotational surfaces with zero Gaussian curvature.
Keywords: Algebraic and Differential Geometry; Cebirsel ve Diferansiyel Geometri